2019
DOI: 10.1590/1980-549720190005.supl.1
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS knowledge among MSM in Brazil: a challenge for public policies

Abstract: Introduction: High level of HIV/AIDS knowledge is required for an effective adoption of preventive strategies. Objective: To assess HIV/AIDS knowledge among men who have sex with men (MSM) in 12 Brazilian cities. Methods: Respondent-Driven Sampling method was used for recruitment. HIV/AIDS knowledge was assessed by Item Response Theory. Difficulty and discrimination parameters were estimated, and the knowledge score was categorized in three levels: high, medium, and low. Logistic regression was used for anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 36 publications
4
37
1
11
Order By: Relevance
“…Overall, median age was 29 years (IQR: [24][25][26][27][28][29][30][31][32][33][34][35][36]. The age distribution of the participants was shifted towards younger MSM (18-24 years) in most of cities in the North, Northeast and Central-west regions, representing almost half of responders from Manaus (46.5%) and Belém (43.1%), the two largest urban areas in the North.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, median age was 29 years (IQR: [24][25][26][27][28][29][30][31][32][33][34][35][36]. The age distribution of the participants was shifted towards younger MSM (18-24 years) in most of cities in the North, Northeast and Central-west regions, representing almost half of responders from Manaus (46.5%) and Belém (43.1%), the two largest urban areas in the North.…”
Section: Resultsmentioning
confidence: 99%
“…A Brazilian study conducted in 2008/9 evaluated HIV knowledge among MSM from 10 Brazilian cities and found that 41% of the sample had lower than average knowledge with participants still reporting beliefs in incorrect modes of HIV transmission such as through the use of a public restroom [33]. In another study conducted in 2016 [34], knowledge was found to vary by region with an overall prevalence of high level of knowledge of 24% that ranged from 5% in Fortaleza to 34% in São Paulo. Importantly, low HIV perceived risk may be a barrier to PrEP uptake [35].…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian study conducted in 2008/9 evaluated HIV knowledge among MSM from 10 Brazilian cities and found that 41% of the sample had lower than average knowledge with participants still reporting beliefs in incorrect modes of HIV transmission such as through the use of a public restroom (33). In another study conducted in 2016 (34), knowledge was found to vary by region with an overall prevalence of high level of knowledge of 24% that ranged from 5% in Fortaleza to 34% in São Paulo. Importantly, low HIV perceived risk may be a barrier to PrEP uptake (35).…”
Section: Discussionmentioning
confidence: 97%
“…there are medicines for HIV-negative people to take to prevent HIV; an HIV-infected person who is taking AIDS medication has a lower risk of transmitting the virus, etc. ), as described in Guimarães et al [39]; (6) perception of risk (low, middle and high), in response to the question: "how do you assess your chance of becoming infected with HIV during your lifetime? "; (7) participation in an…”
Section: Study Variablesmentioning
confidence: 99%